PENGARUH PENAMBAHAN KURKUMA PADA TUBIFEX sp TERHADAP PERTUMBUHAN LARVA IKAN BETOK (Anabas testudinius) - Heltonika, Benny; Sukendi, Sukendi; Hartati, Ria (Fakultas Perikanan dan Kelautan, Universitas Riau, 2016)
Climber perch an economic fish in Sumatera and Kalimantan, culture this fish is still rarely, its problem because larvae still get from natural. Necesity of larvae with good quality to be important to aquaculture activity. Many research have been to done to willing quality larvae. Aimed of this research was improvement of climbing perch larvae trough feed (Tubifex sp) wich enrichment with curcumin. Result of this research shown that the 4rd treatment (enrichment Tubifex sp with 3 mg curcumin) gave best growth on length and weight.